Transforming the rural : global processes and local futures - Bjørkhaug, Hilde; Miele, Mara; Higgins, Vaughan, 1974-; Truninger, Mónica (Bingley : Emerald Publishing Limited, 2017)
This book analyses the key global processes transforming rural spaces in the early 21st century - financialization; standardization; consumption, and commodification. Through detailed case studies, the book examines why these processes are important, how they work in practice, and the challenges they raise as well as opportunities created.
In recent decades, globalization has transformed rural societies and economies across the world. Much has been written by social scientists about the actors and structures underpinning these transformations and the effects on particular social groups, organizations and industries. Yet, to date much less attention has been given to the specific global processes that are fundamental to contemporary rural change. Rural Change and Global Processes provides a systematic analysis of the key global processes transforming rural spaces in the early 21st century - financialization; standardization; consumption, and commodification. Through detailed case studies, the book examines why these processes are important, how they work in practice, and the challenges they raise as well as opportunities created. The book will be of particular relevance to researchers, graduate students, and policy-makers interested in the implications of global processes for rural people and livelihoods.
The financialization of farming: the Hancock company of Canada and its embedding in rural Australia / Sarah Ruth Sippel, Geoffrey Lawrence and David Burch -- Impacts of financialization on agricultural and rural investment: lessons from the Portuguese case / Manuel Belo Moreira -- The chicken game: organization and integration in the Norwegian agri-food sector / Hilde Bjørkhaug, Jostein Vik and Carol Richards -- Re-ordering the rural? Canada, dairy supply management and the Trans-Pacific Partnership negotiations / Bruce Muirhead -- Standards and their problems from technical specifications to world-making / Lawrence Busch -- Creating actionable knowledge for sustainability: a case of "standards in the making" / Allison Loconto and Marc Barbier -- Legitimation and de-legitimation in non-state governance: Leo-4000 and sustainable agriculture in the United States / Maki Hatanaka and Jason Konefal -- Farmer's freedom in the productive world order: standard takers, contesters and negotiators, or dissenters? / Minna Mikkola -- A blog on the landscape: consensus and controversies on wind farms in rural Portugal / Ana Delicado, Mónica Truninger, Elisabete Figueiredo, Luís Silva and Ana Horta -- Changing the olice oil value chain: food regime and development in Portugal / Dulce Freire -- Consuming rural connections: tracing leeks back to their roots / Moya Kneafsey, Laura Venn and Elizabeth Bos -- Consuming animals, constructing naturalness / Mara Miele -- Return to the land: decommodification of local foods in south Italy / Annamaria Vitale and Silvia Sivini -- Nutrition and the mediterranean diet: a historical and sociological analysis of the concept of a 'healthy diet' in Spanish society / Cecilia Díaz-Méndez and Cristobal Gómez-Benito -- School meals and the rural idyll: children's engagements with animals, plants and other nature / Mónica Truninger and Ana Horta.
Includes bibliographical references and index.
Print version record.
Master record variable field(s) change: 072
Keywords: Globalization -- Economic aspects; Rural population; Sociology, Rural; BUSINESS & ECONOMICS -- International -- Economics; BUSINESS & ECONOMICS -- International -- General; Rural communities; Globalization -- Economic aspects; Rural population; Sociology, Rural; Electronic books